Pengaruh Budaya Organisasi dan Gaya Kepemimpinan Terhadap Kepuasan Kerja dan Dampaknya Terhadap Kinerja Karyawan PT. Asuransi Jasa Indonesia (Persero) Kantor Pusat - Zurlisa dan Tantyo Setyowati (Fakultas Ekonomi Universitas Borobudur, 2017)
This study aims to determine the extent of the influence of organizational culture, leadership style on employee performance through job satisfaction in PT. Asuransi Jasa Indonesia (Persero) Head Office. Data processing method using path analysis (path analysis) using SPSS version 22.0. Statistical testing using individual parameter significance test (t test) and simultaneous significance test (Test F). The results showed that simultaneous variable organizational culture, leadership style and job satisfaction have a significant effect on the performance of the partial karyawan.Secara indicate that the first analysis: organizational culture variables significantly influence employee performance, while the second analysis: leadership style variables significantly influence employee performance and on the analysis of 3: job satisfaction variables significantly influence employee performance.